Donation thru SMS - Ku Ahmad, Abdul Halim (Universiti Teknologi Petronas, 2005)
The main objective ofthis project is to develop asystem for donation could happen thru SMS system. This project will concern on developing an integrated system to allow SMS being transferred via mobile phone gateway to enable mobile phone user make a donation thru sending SMS. This system will display out the main components such SMS data management system, SMS server itself and tools being used to run the system. The entire introduction, problem statement, objectives, and the scope ofthe studies for the project will be further explained. This document also gives related information about the system in literature review section. This section presents several judgments from journalist and professional writer that relate to the project topic. The proposed methodology is then discussed in the next section. This section also includes the tools and hardware that are to being used in developing the system. InResult and Discussion part, I had explained about my findings and results ofmy work during four month I've develop this project. I had done some research regarding this area and gather all the data. The outcome ofthis project is a good SMS system design for donation business could be implemented in easy and effective way